Analysis of the Circular Economy's Implementation at Maggot House Mengger Sub-District Bandung City - Rochaeni, Anni; Ardianti, Dhini; Suryana, Popo; Ardiani, Winda P.; Habibie, Panji A.; Fadhlan, M. Razkia; Nurnazmi, Alvi; Syahrani, Aura P (Journal of Community Based Environmental Engineering and Management, 2024)
In 2023, the city of Bandung faced serious problems because the Sarimukti landfill caught fire and the city of Bandung experienced a "waste emergency". One of the programs launched is the construction of maggot houses in every sub-district in Bandung City with a target of processing 1 ton of organic waste/day. Mengger Sub-district is one of the sub-districts that received assistance to build maggot house. The land area of ​​the maggot house is 150 m2, managed by 4 officers. This study aims to identify various problems that must be resolved first so that the circular economy concept can be implemented at the Mengger Maggot House. The study was carried out by conducting observations, detailed surveys and in-depth interviews with various stakeholders in Mengger Sub-district. Observations were carried out to see the level of compliance of residents in sorting, a detailed survey was carried out on the waste collection and processing system at the maggot house, and in-depth interviews were conducted with assistants from Bandung City Environmental Service Office (DLH), maggot buyers, sub-district officials, maggot house officers, neighbourhood (RT) and hamlet (RW), and waste collector. Based on the results of observations, it was found that only some residents carry out sorting consistently, a collection system already exists in each RT/RW but they have not implemented a segregated waste collection system, and there is no system for transporting waste from the RW to the maggot house so that the amount of organic waste entering the maggot house is still low, no electricity and clean water, no choppers, leaks in the fly cage, and no diversification in maggot products. Through various socialization activities and Focus Group Discussions with all stakeholders, various agreements were obtained to resolve various problems at the Mengger Maggot House.